Experiment of Dielectric Frequency Response for Aged ZnO Surge Arrester - Aiamrungruang, Phitthaya; Methavithit, Winai; Pannil, Pittaya; Chuayin, Chaitawat; Zinck, Matthieu; Jeenmuang, Siwakorn; Pattanadech, Norasage; Bunlaksananusorn, Chanin (My University, 2025)
Condition-based monitoring of surge arresters has gained increasing attention in modern power system asset management, especially for medium-voltage equipment. This paper presents an investigation into the dielectric frequency response (DFR) analysis technique as a diagnostic method to evaluate aging and unhealthy conditions in 21-kV metal oxide surge arresters (MOSA). Four types of simulated defects, excessive number of lightning current stress, cracking, moisture ingress, and tracking, were introduced to represent common field failures. The DFR technique enables frequencydomain interpretation of dielectric properties, providing insight into insulation behavior over a wide frequency range. The test results show a significant variation in capacitance and dissipation factor corresponding to different defect types. Among these, moisture ingress exhibited the most severe deterioration. The findings suggest that DFR is a viable offline diagnostic method that can support preventive maintenance strategies for high-voltage surge arresters.
Keywords: aging condition; dielectric frequency response; frequency domain analysis; insulation diagnosis; metal oxide surge arrester